The Nexus between Urbanization, Energy Demand and Healthcare in Bangladesh - Rahman, Saanjaana (Journal of Social Economics Research, 2019)
Urbanization leads to increase in energy usage as it aggravates the demand of housing, land usage, commutation and many more. Economic theory postulates that urbanization is a demographic activity where a big share of any country’s people migrates in urban settlements (Arouri et al., 2014). The energy demand will keep on increasing in the upcoming years as targets for development and economic growth aggravates. Bangladesh aims to become a middle-income nation by 2021. As more and more workers will migrate to the urban city for job, they will use more and more healthcare facilities available in the city, which in turn will increase the demand for energy. Healthcare industry is termed as a vital sector for any country, as health is wealth for any nation. Furthermore, patients’ health and quality of life is important to perform economic activities or to be an active citizen of the country for growth of the economy, as a healthy economy is the key to a successful nation. Good governance is important in this aspect as the country has set a target to gain universal health coverage by 2023 to pay 70% of the medical expenses. However, healthcare industry needs to utilize renewable energy and smart technology for the sustained economic growth.